A study on photovoltaic parameters of mono-crystalline silicon solar cell with cell temperature. (November 2015) - Chander, Subhash; Purohit, A.; Sharma, Anshu; Arvind; Nehra, S.P.; Dhaka, M.S.
Abstract: In this study, the effect of cell temperature on the photovoltaic parameters of mono-crystalline silicon solar cell is undertaken. The experiment was carried out employing solar cell simulator with varying cell temperature in the range 25–60 °C at constant light intensities 215–515 W/m 2 . The results show that cell temperature has a significant effect on the photovoltaic parameters and it controls the quality and performance of the solar cell. The open circuit voltage, maximum power, fill factor and efficiency are found to be decreased with cell temperature. The reverse saturation current increases with cell temperature and a slight increment is observed in the short circuit current. The temperature coefficient of the open-circuit voltage, fill factor and maximum output power is found to be negative while positive for the short circuit current. The relative change study of photovoltaic parameters with temperature is also undertaken. The relative changes are found from −0.0022/°C to −0.0025/°C, 0.002/°C, −0.0013/°C and −0.002/°C for open circuit voltage, short circuit current, fill factor and maximum output power respectively. The results are in good agreement with the available literature.